Can Naked Singularities Exist Without Violating The Laws of Black Hole Thermodynamics? (JOURNAL OF ADVANCES IN PHYSICS, 2021)
According to the cosmic censorship conjecture, it is impossible for nature to have a physical singularity without a horizon because if it were to arise in any formalism, for instance as an extremal black hole (Kerr or Reissner-Nordstrom) then the surface gravity κ = 0, which is a strict violation of the third law of black hole thermodynamics. In this paper we explore whether a true singularity can exist without defying this law.